Influence of asymptotic corrector on the description of the dynamic behaviour of a circular elastic plate (Archives of Mechanics - Test, 2004)
The aim of the present paper is to study an initial-boundary value problem for an isotropic circular plate. General theory was developed by the authors in [12]. The novelty consists in the study of influence of second-order terms (correctors), obtained by variational-asymptotic analysis, on the dynamic solution of plates.